2016
DOI: 10.1136/bcr-2016-214895
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic (SIL) sigmoid colectomy and uterus-preserving repair for colo-uterine fistula secondary to severe diverticular disease: an unusual technical solution for an unusual presentation of a common disease

Abstract: Colouterine fistula as a potential complication of chronic diverticulitis is a rare entity with less than 30 cases reported worldwide. Generally, patients require a multidisciplinary approach including a major laparotomy with hysterectomy and sigmoid colectomy, and, occasionally, temporary colostomy. We report the first attempt of a novel, minimally invasive technique for managing a case of benign colouterine fistula with single-incision laparoscopic (SIL) sigmoid colectomy and uterus preservation. A small, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Others even suggested simple percutaneous drainage of the uterus after colonic diversion Some even advocate just simply primarily suturing the colon after separating the viscera closing the uterine perforation. More surgeons prefer resection to examine the complete specimen for the purpose of diagnosing potential malignancies, both on the sigmoid and the uterine side [ [30] , [31] , [32] ]. Some authors have pointed out that fistulas involving the colon in elderly patients are more likely to be managed conservatively than in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Others even suggested simple percutaneous drainage of the uterus after colonic diversion Some even advocate just simply primarily suturing the colon after separating the viscera closing the uterine perforation. More surgeons prefer resection to examine the complete specimen for the purpose of diagnosing potential malignancies, both on the sigmoid and the uterine side [ [30] , [31] , [32] ]. Some authors have pointed out that fistulas involving the colon in elderly patients are more likely to be managed conservatively than in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first attempt of a novel, minimally invasive technique for managing a case of benign colouterine fistula with single-incision laparoscopic (SIL) sigmoid colectomy and uterus preservation was reported. Findings showed that single-incision laparoscopy in complicated diverticular disease and fistula formation cases is a challenging but technically feasible option in experienced hands (46). The safety and efficacy of one-stage single-incision laparoscopic-assisted anorectoplasty (SILAARP) as an alternative to the conventional approach was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In six cases, colectomy and closure of the fistula were performed (Table ). Two cases were treated laparoscopically: one by sigmoidectomy combined with closure of the fistula, and the other via low anterior resection with colostomy and fistula closure .…”
Section: Discussionmentioning
confidence: 99%
“…Uterus excision or fistula closure without uterus excision is controversial for the treatment of non‐tumorous uterine fistula. Tracy et al and Banky et al both reported successful laparoscopic colectomy and fistula closure without uterus excision . Factors related to selecting patients for fistula closure or uterus excision include the patient's age and general condition as well as the extent of the inflammation around the uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation